Pembuatan Grease Dari Minyak Biji Karet : Mempelajari Pengaruh Campuran Lioh-Ca(OH)2 Dan Rasio Base Oil - Septiani Lestari; Irdoni Irdoni; Nirwana Nirwana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Grease is a semi-solid lubricant that is given between two metal objects that move independently or one of the moving objects while the other is stationary with the aim of reducing friction. Grease is applied to industrial and automotive machinery. Rubber seed oil is non edible oil because it is toxic, so it has the potential to be a grease. This research aims to make grease using rubber seed oil, studying the effect of ratio mol metal LiOH:Ca(OH)2, as well as the effect of comparison of metal soap:base oil on the quality and characteristics of grease. The research stage is: raw material preparation includes extraction of rubber seed oil by pressing method, then degumming process using phosphoric acid (85%) 0.5% (w/w), temperature of 90oC, for 1 hour and centrifuge for 20 minutes. Then the process of making metal soap (thickening agent), 100 ml of rubber seed oil is heated to a temperature of 70oC, then added LiOH:Ca(OH)2 metal while stirring with a stirring speed of 650 rpm for 30 minutes. Furthermore, the process of making grease, rubber seed oil as a base oil is mixed with metal soap (thickening agent) according to predetermined variables. The mixing process was carried out at a temperature of 70oC then metal soap (thickening agent) was added to the reactor and stirred with a stirring speed of 650 rpm for 30 minutes, after the temperature of the mixture reached 120oC additives added 5% w/w and a stirring time of 3.5 hours. Then the grease test is carried out, namely the dropping point test based on ASTM D566 and the penetration test based on ASTM D217. The best results on the soap formula 90%:10% and the grease formula 75%:20%:5% obtained dropping point 145oC, penetration 240 (0.1 mm) and NLGI 3.Keywords: grease, rubber seed oil, dropping point test, penetration test